Analisis Manajemen Risiko Ancaman Kejahatan Siber (Cyber Crime) Dalam Aplikasi Whatsapp - Reni Kuswulandari; Axzara Wirid Isra Jowanka; Telaga Nabila Putri Riyanto; Titin Listiani (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
Cybercrime has become a significant threat in today's digital age. The existence of WhatsApp is also vulnerable to various security risks and cybercrime threats. Lack of knowledge about awareness to be careful playing social media makes not a few users become victims of cybercrime. This research aims to conduct an in-depth analysis of the cybercrime risks that can affect WhatsApp users and provide appropriate preventive measures to reduce the negative impact of these threats. The method used in this research is qualitative with in-depth research using observation to observe and study user behavior. Based on the data analysis in this study, the stolen data ranges from personal information and SMS to confidential banking information such as one-time passwords (OTP).